Foliar Nutrition, Biostimulants and Prime-Like Dynamics in Fruit Tree Physiology: New Insights on an Old Topic - Tanou, Georgia; Ziogas, Vasileios; Molassiotis, Athanassios (Frontiers in Plant Science, 2017)
Despite the fact that the usage of foliar nutrients has long history, many aspects of fertilization through leaves are still unknown. Herein, we review the current knowledge regarding the canopy fertilization putting special emphasis on Fe nutrition and briefly provide insights into the nanofertilizer technology of the foliar feeding of fruit crops. Examples of how foliar fertilization can be used for enhancing the tolerance against abiotic stress are provided. In addition, this paper discusses the main aspects of the foliar application of biostimulants regarding crucial factors of fruit cropping systems, such as fruit yield/size, tolerance to environmental stresses and nutrient availability. Also, we specifically discuss the role of hydrogen peroxide (H2O2) and nitric oxide (NO) as priming molecules and their possible cross-talk with biostimulants in fruit tree physiology. Finally, a view of the key issues for future fundamental and applied research in the topic is put forward.